Developing an instrument of national examination of equivalency education Package C of mathematics subject - Ian Harum Prasasti; Edi Istiyono (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2018)
The national examination of equivalency education is a competency test to equalize non-formal education with formal education. Departing from the importance of the quality and expectations of the national examination of equivalency education package C mathematics subjects and because the results are inseparable from the implementation process, developing an evaluation instrument to assess the implementation of the national examination of equivalency education package C mathematics subjects is important. The purpose of this study is to develop a suitable instrument for conducting an evaluation of the national examination implementation of the equivalency education package C mathematics subject. The respondents in this research are package C test takers in Bantul Regency, Yogyakarta. The data were analyzed by using SPSS 20.0 and Lisrel 8.54. The result of the analysis shows (1) based on the data obtained from respondents of try-out, the developed instrument is valid, reliable and qualified as a fit model; (2) components in the instrument of test takers is learning time, socialization, test materials, and test venue; and (3) the instrument have the validity value of 0.40 and reliability coefficient of 0.70.